White Columns Update 1987-1988. (New York : White Columns, 1988)
McMahon, Paul ; Fleishman, Jill ; Pleasants, Craig ; Carlson, Sue ; Downsbrough, Peter ; Denker, Amber ; Akin, Gwen ; Ludwig, Allan ; Broughel, Barbara ; Robertson, Josie ; Jenkins, Jeffrey ; Pearlstein, Alix ; Noland, Cady ; Pavlow, Bruce ; Gimblett, Max ; Kuebel, Cynthia
White Columns Update 1987-1988, White Columns, New York, May 21- June 25, 1988
boek